Some aspects of molecular diagnostics in Lynch syndrome - Kurzawski, Grzegorz (Contemporary Oncology/Współczesna Onkologia, 2006)
This manuscript is composed of five parts which summarize five publications in succession. Essentially, they are concerned with molecular diagnostics of Lynch syndrome and are based on studies in 238 families. The finding that young age at diagnosis is the key feature in patients with MSH2 and MLH1 mutations (Part 1) has helped to define simple criteria for the preliminary diagnosis of this syndrome. A cheaper method for the detection of mutations has been developed (Part 2) and applied to study the types of mutations and their prevalence in Poland (Part 3) and the Baltic States (Part 4). A specific feature of these mutations, i.e. presence of recurrent mutations in the majority of affected families with mutations, has suggested the feasibility of effective diagnostics with a single test disclosing all of them. An attempt to reveal other causes of familial aggregation of colorectal cancer has ruled out any association with C insertion in the NOD2 gene (Part 5).